Spiritual well-being in a group of South African adolescents - Van Rooyen, Brenda Mary (University of the Free State, 2007)
Findings in this South African sample of adolescents confirm that adolescents who highly value religion/spirituality also report both praying and attending church/spiritual activities more frequently. Thus there is congruence between their commitment, and their practices – both personal (prayer) and public (church/spiritual activity attendance) – associated with positive psychological outcomes (Pargament, 1997). Whether belief precedes practice or practice precedes belief is arguable (Spilka et al., 2003), but this research supports evidence of a correspondence between belief and practice. This research also suggests that a high valuing of religion/spirituality, more frequent church/spiritual activity attendance and more frequent prayer are all related to higher levels of transcendental spiritual well-being or a self-reported significant and harmonious relationship with a divine Other or energy. Thus commitment to spirituality and public and private practices associated with spirituality seems to generate a closer relationship with the divine and thus higher levels of transcendental spiritual well-being. Similarly this research suggests that a higher valuing of religion/spirituality and more frequent prayer are related to higher levels of personal spiritual well-being and to higher levels of global spiritual health. Thus commitment and private practice, more consistent with an intrinsic religious orientation (Allport & Ross, 1967; Milevsky & Levitt, 2004; Pargament, 1997), seem related to a closer relationship with self and to more developed relationships in all domains (personal, communal, environmental and transcendental) generating higher levels of spiritual health.
Thesis (Ph.D. (Child Psychology))--University of the Free State, 2007
Keywords: Spiritual formation; Teenagers -- Psychology; Teenagers -- Religious life